2004
DOI: 10.1007/s00436-003-1034-z
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma avium: experimental transmission from black flies to canaries

Abstract: Trypanosomes identified as Trypanosoma avium were found in the ornithophilic black flies ( Eusimulium latipes) attacking buzzard nestlings ( Buteo buteo). Parasites formed plugs and rosettes in the hindgut of the vector and were attached on the cuticular lining of the black fly anterior intestine (ileum) by hemidesmosome-like plaques. Hindgut stages from infected black flies were experimentally transmitted into canaries ( Serinus canaria) by ingestion of vectors and by contamination of host conjunctiva. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 17 publications
(25 reference statements)
1
51
0
1
Order By: Relevance
“…Volf et al (2004) reported that trypanosomatid parasites block the stomodeal valve in Culex quinquefasciatus causing regurgitation which facilitates parasite transmission to the vertebrate host during blood feeding by a mechanism similar to that for Leishmania . In other experiments, Trypanosoma avium was transmitted to canaries ( Serinus canaria ) by black flies ( Eusimulium latipes ) by ingestion of infected black flies and by contamination of host conjunctiva (Votypka and Svobodova, 2004). Additionally, Trypanosoma culicavium was successfully transmitted from C. quinquefasciatus to birds by ingestion of infected mosquitoes but not the bite of infected mosquitoes (Votypka et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Volf et al (2004) reported that trypanosomatid parasites block the stomodeal valve in Culex quinquefasciatus causing regurgitation which facilitates parasite transmission to the vertebrate host during blood feeding by a mechanism similar to that for Leishmania . In other experiments, Trypanosoma avium was transmitted to canaries ( Serinus canaria ) by black flies ( Eusimulium latipes ) by ingestion of infected black flies and by contamination of host conjunctiva (Votypka and Svobodova, 2004). Additionally, Trypanosoma culicavium was successfully transmitted from C. quinquefasciatus to birds by ingestion of infected mosquitoes but not the bite of infected mosquitoes (Votypka et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…avium is transmitted by blackflies ( Simulium spp.) by ingestion or via conjunctiva [5, 6], T. corvi is transmitted by ingestion of hippoboscid flies ( Ornithomyia avicularia ) [7, 8]. Mature stages of T. culicavium are localised on the stomodeal valve of Culex mosquitoes, suggesting inoculative transmission; however, birds get infected by ingestion of the vector as well [2].…”
Section: Introductionmentioning
confidence: 99%
“…n. Many workers implicate biting midges (together with black flies and mosquitoes) as carriers of bird trypanosomes with transmission through contamination or ingestion of the vector (posterior station transmission) (Bennett 1961, 1970, Desser et al 1975, Baker 1976, Miltgen & Landau 1982, Votypka & Svobodová 2004. However metacyclic trypomastigotes were noted in the mouth parts and salivary glands of some of the vectors and inoculative experiments showed that these forms were infective (Bennett 1970, Baker 1976.…”
Section: Discussionmentioning
confidence: 99%